Cultural values and career goal of Gen-X and Gen-Y employees: evidence from selected Malaysian companies - Ismail, Maimunah; Abd Rahim, Atikah Nadia; Kim, Hou Lee; Mohd Thahri, Nurul Fariza (Faculty of Economics, Vilnius University, 2016)
This paper seeks to compare the influence of dimensions of cultural values of self-enhancement, self-transcendence, conservation, and openness to change on career goal among Gen-X and Gen-Y employees in selected Malaysian industrial companies. This study used the Social Cognitive Career Theory as its underlying theoretical framework. A total of 264 personnel from oil and gas, information, communication and technology (ICT), as well as banking and insurance companies participated in the study of whom 48 and 216 are Gen-X and Gen-Y employees, respectively. The multiple linear regression analysis found self-enhancement and conservation predicted significantly the career goal of Gen-X; while self-enhancement, self-transcendence, conservation predicted significantly the career goal of Gen-Y, with the explanatory power of the former (33%) being greater than the latter (28%). Recommendations for human resource management and future research are discussed.